Analysis of factors influencing the willingness to sell forest carbon sink products online: a case Study of Fujian Province, China - Ren, Xiaojin; Tan, Yunshu; Zheng, Yidan; Chen, Qin (Frontiers in Forests and Global Change, 2025)
Farmers’ willingness to sell forest carbon sink products through the Internet is of great practical significance for achieving the goals of carbon peaking and carbon neutrality and promoting the sustainable development of forestry. Based on 300 sets of farmer survey data from Fujian Province, this study takes resource endowment as the core explanatory variable, and constructs a multiple ordered Logistic model by combining natural, human, and social resource endowments to empirically analyze the factors influencing farmers’ willingness to sell carbon sink products through the Internet. The research results show that the per capita forest land area of the household, carbon knowledge training, whether the farmer is a village cadre, and awareness of Internet sales of forest carbon sinks all have a significant impact on farmers’ willingness to sell through the Internet. In addition, control variables such as household forestry income and forestry operation activities also have varying degrees of influence on the willingness to sell through the Internet. This paper enriches the influence mechanism of resource endowment on the behavior of farmers in the carbon sink market and provides new empirical evidence for the formulation of carbon sink market policies. Based on this, it is necessary to rely on the advantages of natural resource endowments to provide targeted support for large-scale farmers, strengthen human resource empowerment by constructing a “knowledge empowerment + risk mitigation” dual-track mechanism, optimize the mobilization of social resources to give play to the demonstration effect of village cadres, and improve market infrastructure to reduce risks and operational thresholds. This will encourage farmers to actively participate, making the Internet sales of forest carbon sink products large-scale and normalized.